2020
DOI: 10.1590/1806-93042020000200009
|View full text |Cite
|
Sign up to set email alerts
|

Indications and reasons for discontinuing the levonorgestrel-releasing intrauterine system (LNG-IUS)

Abstract: Objectives: to identify the main indications and reasons for discontinuing the use of the Levonorgestrel-Releasing Intrauterine System (LNG-IUS). Methods: a cross-sectional study was carried out from medical records of 327 women who used the LNG-IUS 52mg between January 2011 and December 2016 at a public hospital in the Northeast of Brazil. Results: the main indications for the use of the LNG-IUS were: contraception (32.7%), myoma/metrorrhagia (28.7%) and endometriosis/pelvic pain (22.3%). Of the 327 women, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Pires et al provided some recommendations and suggested reasons for discontinuing the use of the LNG-IUS system [ 25 ]. The published survey also showed that only 32.7% of IUDs are used for contraceptive purposes.…”
Section: Main Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Pires et al provided some recommendations and suggested reasons for discontinuing the use of the LNG-IUS system [ 25 ]. The published survey also showed that only 32.7% of IUDs are used for contraceptive purposes.…”
Section: Main Evidencementioning
confidence: 99%
“…The total number of beneficiaries was 47,768,176. A total of 53.09% (25,358,355) of beneficiaries were female, of whom 22.87% (5,799,229) were children or adolescents (aged 0-19 years), 43.39% (11,001,855) were adult and fertile women (20-44 years), and 33.75% (8,557,271) were mature or elderly women (45-80 years or more) [34]. To this number, we applied the percentage of general contraceptive use (84.8%, as identified by Lago et al).…”
Section: Pharmacoeconomic Analysismentioning
confidence: 99%
“…Desse modo, promove-se o bloqueio gonadotrófico, em especial no pico de LH, impedindo por fim, a ovulação. (PIRES, et al, 2020) Sendo assim, o principal objetivo deste estudo é a análise e comparação entre os fármacos citados para avaliar os efeitos adversos, eficácia e aceitação destes pelas mulheres.…”
Section: Introductionunclassified